Didactic Conditions And Model Of Development Of Students' Intercultural Communication Competence - Maxsudaliyeva Ra’noxon Baxodir qizi (Euro Asian Journal Publishing, 2024)
This article investigates the effectiveness of specific didactic conditions and a three-stage developmental model in fostering students' intercultural communication competence (ICC). The study employs a mixedmethods approach, combining quantitative and qualitative data to provide a comprehensive understanding of the research problem
Keywords: didactic conditions; three-stage developmental model